ANALISIS PENDAPATAN PETERNAK SAPI PERAH KECAMATAN BANYUMANIK, KECAMATAN GETASAN, DAN KECAMATAN CEPOGO - Dinar Anindyasari; A Setiadi; T Ekowati (MEDIAGRO, 2015)
The purpose of this study was to knowing the income of dairy farmers Banyumanik District, Getasan District, and Cepogo District, knowing the difference of dairy farmers income Banyumanik District, Getasan District, and Cepogo District. Research was held in June-November 2014. Taking the location of the study area with purposive sampling where criteria districts that have  dairy cattle business. The method used in this research was a survey method. The respondents were chosen by random sampling method. There were 240 farmers of dairy cattle farmers were chosen in this research.  The primary data were obtained directly through observation at the farm activities and interviews with respondents using a questionnaire that has been prepared. Data analysis used analysis of income formula and K-independent test. The results showed that the average income in farmers Banyumanik District was IDR. 1,070,131.00/month, farmers in Getasan District was IDR. 1,345,852.00/month and farmers Cepogo District was  IDR. 1,514,953.00/month. The result showed of k-independent test that the farmers income in Banyumanik District, Getasan District, and Cepogo District.   Keywords: Dairy farmers, income, k-independent test